Analisis Program Pengembangan Agrobisnis Holtikultura dengan Metode Policy Analysis Matrix - Budiman Notoatmojo; Haryadi Sarjono (The Winners, 2006)
In general, article present an evaluation to find out how far does the development program of agribusiness based on horticultural plant production succeed. This evaluation program uses macro indicator including production development and the productivity of horticultural commodity, the development of national add value, and the contribution to the independency of the national logistic. While the micro indicator includes the profitability level of the horticultural agribusiness, competitive level, and theissues and problems that must be faced while the PPAH program is in progress.